Unilateral Endoscopic and Unilateral Biportal Endoscopic surgery for lumbar spinal stenosis: a systematic review and meta-analysis - Li, Kun; Zhang, Zhibin; Ran, Jiangyu; Ma, Liang; Meng, Xiangyu (Frontiers in Surgery, 2025)
ObjectiveLumbar spinal stenosis (LSS), the most frequently occurring degenerative spinal disease, significantly affects patient well-being. Preliminary clinical studies indicate favorable outcomes from unilateral biportal endoscopy (UBE) and unilateral endoscopy (UE) for managing LSS. This meta-analysis assessed the clinical effectiveness and safety profiles of unilateral laminotomy for bilateral decompression (ULBD) via these two minimally invasive endoscopic methods, aiming to establish evidence-based clinical recommendations.Materials and methodsA thorough examination of electronic databases was performed, encompassing PubMed, Cochrane Library, Web of Science, Embase, Medline, CNKI, WanFang, and VIP. Research assessing the clinical outcomes and complications of UBE-ULBD compared to UE-ULBD in the treatment of LSS was deemed suitable for inclusion. The outcome measures extracted comprised the Visual Analogue Scale (VAS), Oswestry Disability Index (ODI), duration of surgery, length of hospitalization, intraoperative blood loss, area of postoperative dural sac expansion, angle of ipsilateral facet joint resection, and occurrences of surgical complications.ResultsSeventeen articles met inclusion criteria, encompassing one prospective cohort study, two case-control studies, and fourteen retrospective studies, involving 1, 457 total patients. The meta-analysis indicated that there were no statistically significant differences observed between the UBE and UE groups in terms of postoperative VAS scores for back and leg pain, as well as ODI scores at the intervals of 1 week, 3–6 months, and 6–12 months (P > 0.05). Nevertheless, the UBE methodology exhibited markedly reduced operative durations (P = 0.005) and enhanced postoperative expansion of the dural sac (P < 0.0001). Estimated intraoperative blood loss, hospitalization duration, complication rates, and ipsilateral facet joint resection angles were comparable between groups (P > 0.05).ConclusionsThe meta-analysis indicates that the UBE technique exhibits similar long-term clinical efficacy, blood loss, duration of hospital stay, and rates of complications when compared to the UE technique. However, the UBE group exhibited shorter surgical duration and greater dural sac expansion area.